ANALISIS YURIDIS KEWAJIBAN NOTARIS MERAHASIAKAN AKTA TERKAIT PASAL 3 PERATURAN PEMERINTAH NOMOR 43 TAHUN 2015 MENGENAI NOTARIS SEBAGAI PIHAK PELAPOR DALAM PENCEGAHAN DAN PEMBERANTASAN TINDAK PIDANA PENCUCIAN UANG - IRA QUWAITY SARAGIH (PREMISE LAW JURNAL, 2016)
The result showed that, regarding the Goverment Regulation No. 43/2015 about informer in the Prevention and Eradication of Criminal Act of Money Laundering, Article 3 of this Goverment Regulation states a notary as as informer to a presumption of money laundering for the deed that he/she has made. Meanwhile, UUJN (Law about Position of Notary)  obliges a Notary to keep the confidentiality of the deeds he/she has made. According to the system hierarchy of statutory law in Indonesian, in line with Article 7 of the Law No.12/2011 about The Establishment of Statute stating that the position of Law is higher than that of the Goverment Regulation. Therefore, principally Goverment Regulation is void to be implemented on a notary as long as he/she carries out his/her duty and function in accordance with the UUJN. Keywords : Notary, Goverment Regulations No.43/2015, Money Lounderin